Psicología de la felicidad y bienestar - Hernández Arteta, Robertha Gabriela (2020)
This article presents a state of the art about the Psychology of happiness and well-being, addressing a first topic related to the beginnings of this psychological paradigm and its development today. It is important to mention that the approach is recent and considers psychology in a very different way from the traditional one, for this reason the main authors of the same are presented such as Seligman, Lyubomirsky and, in Peru, Yamamoto; in addition to different theoretical perspectives of this approach. Rosales (2018, p. 1) indicates that, at present, elements such as well-being and happiness in life are two concepts of vital importance not related to pathological elements, but, on the contrary, are related to subjective aspects of daily living. Based on this notion, the author indicates, various questions have arisen related to how to know if a person… (a) it feels good; (b) possesses optimal well-being; or (c) has a positive perception of happiness that improves quality of life. Now, Rosales (ibid., p.1) adds that the perception of these elements Will depend, to a great extent, on the age, gender, context and stage of development of this person. A second theme developed in this state of the art is the treatment of various psychological models an the intervention of each one in the human being, from the neurological, cognitive, behavioral, and humanistic approach. In the same way, diverse investigations are approached at a national an international level that conclude in the relevance of focusing on the positive aspectcs of the individual. The general result of the present study indicates a satisfactory level in terms of psychological well – being and hapiness, which allows us to decude that this new trend of psychology is becoming a very important área, since different subareas converge in it and guarantees better results in the human being in the aspects where it is related.